(untitled) (American Journal of Business Management, Economics and Banking, 2026)
Problem loans, also known as non-performing loans, are one of the main challenges faced by commercial banks as they have a direct impact on efficiency and financial stability. A high level of problem loans reduces bank profitability, weakens capital adequacy, and limits the ability of banks to provide credit to the economy. In recent years, many countries have implemented effective measures to reduce the share of problem loans through regulatory reforms, improved credit risk management, and the use of special institutional mechanisms.